REGENERASI ALAMIAH DI KAWASAN REVEGETASI PASCA TAMBANG BATUBARA - Noor, Ahmad Sugian; Hatta, Gusti Muhammad; Kissinger, Kissinger; Suyanto, Suyanto (Universitas Lambung Mangkurat, 2021)
Revegetation can trigger a succession process in post-mining land. The success of revegetation can be assessed by increasing the natural species in the revegetation area. The research objective was to analyze the natural regeneration of mines from several revegetated areas with different planting ages (2 years, 4 years, 6 years, and 8 years). The research was conducted in the post-coal mining revegetation area of PD. Baramarta, Sungai Pinang District, Banjar Regency, South Kalimantan. Data collection was carried out using the nested plot method by making 6 plots measuring 20m x 20m. The data collected were the number of species, the number of individuals and the diameter of poles and trees. Data analysis used tabulated matrices and Importance Value Index. The results showed there were 11 plant species in the revegetation area, 7 natural plant species, 3 main plant species and 1 secondary plant species. Natural vegetation regeneration is only found at the seedling and sapling level. L.indica and C. longifoliium, based on Importance Value Index, are natural vegetation types that dominate the vegetation structure of revegetation areas. Main plant types A.mangium and P. falcataria are able to regenerate naturally. Limited habitat in post-coal mining areas has limited natural regeneration in revegetation areas. Increasing the diversity of revegetation plant vegetation can be done through enrichment planting